COMPLICATIONS IN LOCAL ANESTHESIA: : WHAT ARE THEY? AND WHAT IS THE PERSPECTIVE FOR THE FUTURE? LITERATURE REVIEW - Silva Pinto, Paulo André da; Zamberlan Rausch, Francismar (Health and Society, 2021)
BACKGROUND: The present work is a review of the literature on the main complications related to local anesthetics and brings what the articles indicate about the incidences of the future. OBJECTIVE: To deal with the main documented complications and, using the available information, draw a picture of future complications. METHOD: The basic information was found in searches in the PubMed, MEDLINE, SciELO and Google Scholar databases. RESULT: Complications found were: Injection pain, needle breaking, trismus, hematoma, infection, edema, necrosis, allergies, intoxication, methemoglobinemia, ophthalmic changes, paraesthesia and complications modulated by systemic changes. The authors conclude that the next few years may have an increase in the impact of complications.